cpubi4 Is Essential for Development and Virulence in Chestnut Blight Fungus - Chen, Qi; Li, Yongbing; Wang, Jinzi; Li, Ru; Chen, Baoshan (Frontiers in Microbiology, 2018)
Ubiquitination plays key roles in eukaryotic growth, stress adaptation, and metabolic regulation. In our previous work, ubiquitin was found to be secreted in the hypovirus-infected strain of Cryphonectria parasitica, a phytopathogenic filamentous fungus responsible for the chestnut blight. Here we report the functional and molecular characterization of a polyubiquitin gene, cpubi4, in C. parasitica. The expression of cpubi4 was upregulated by the infection of a hypovirus. Deletion of cpubi4 resulted in abnormal morphology, reduced sporulation, attenuation of virulence, and significant reduction in ubiquitination. A total of 378 sites in 236 proteins were identified to be significantly decreased in ubiquitination in the absence of cpubi4. Quantitative proteome analysis revealed that 285 in 4776 identified proteins changed in abundance (1.5-fold, P<0.05) in the cpubi4 null mutant, as compared with the wild-type strain.